Changes in sympathetic nervous system activity after renal denervation: results from the randomised Oslo RDN study. (4th May 2021) - Undrum Bergland, Ola; Larstorp, Anne Cecilie K.; Lund Søraas, Camilla; Høieggen, Aud; Rostrup, Morten; Norheim Kjaer, Vibeke; Godang, Kristin; Sevre, Knut; Fadl Elmula, Fadl Elmula M.
Abstract: Purpose: Sympathetic nervous system (SNS) over-activity is associated with essential hypertension. Renal sympathetic denervation (RDN) possibly lowers office- and ambulatory blood pressure (BP) in patients with treatment-resistant hypertension (TRH). We aimed to assess the effect of RDN compared to drug adjustment on SNS activity among patients with TRH by measuring plasma catecholamines and heart rate variability (HRV) during stress tests. Materials and methods: Patients with TRH were randomised to RDN ( n = 9) or Drug Adjustment (DA) ( n = 10). We measured continuous HRV and beat-to-beat-BP using FinaPres® and obtained plasma catecholamines during standardised orthostatic- and cold-pressor stress tests (CPT) before- and six months after randomisation. Results: CPT revealed no differences between groups at baseline in peak adrenaline concentration (69.3 pg/mL in the DA group vs. 70.0 pg/mL in the RDN group, p = 0.38) or adrenaline reactivity (Δ23.1 pg/mL in the DA group vs. Δ29.3 pg/mL in the RDN group, p = 0.40). After six months, adrenaline concentrations were statistically different between groups after one minute (66.9 pg/mL in the DA group vs. 55.3 pg/mL in the RDN group, p = 0.03), and six minutes (62.4 pg/mL in the DA group vs. 50.1 pg/mL in the RDN group, p = 0.03). There was a tendency of reduction in adrenaline reactivity after six months in the RDN group (Δ26.3 pg/mL at baseline vs. Δ12.8 pg/ml after six months, p = 0.08), while it increased in the DA group (Δ13.6 pg/mL at baseline vs. Δ19.9 pg/mL after six months, p = 0.53). We also found a difference in the Low Frequency band at baseline following the CPT (667µs 2 in the DA group vs. 1628µs 2 in the RDN group, p = 0.03) with a clear tendency of reduction in the RDN group to 743µs 2 after six months ( p = 0.07), compared to no change in the DA group (1052µs 2, p = 0.39). Conclusion: Our data suggest that RDN reduces SNS activity after six months. This finding warrants investigation in a larger study. Clinical Trial Number registered at www.clinicaltrials.gov : NCT01673516